Reevaluation and taxonomic clarification of Gigantopteridium and Cathaysiopteris of western equatorial Pangea and their biogeographical significance. (20th July 2017) - Koll, Rebecca A.; DiMichele, William A.; Manchester, Steven R.
Abstract: A reassessment of the taxonomic relationships of North American gigantopterids is presented in light of an examination of large populations of specimens housed in the US National Museum of Natural History. Variations in venation and subtle aspects of leaf shape facilitate refined understanding of the relationships and diversity of the North American gigantopterid species leading to an improved understanding of the taxonomic and biogeographic relationships of this group, which are found most abundantly in western equatorial Pangea and Cathaysia. Current literature suggests that there are eight North American genera, however, this study has revealed a morphological overlap of several previously defined genera, leading to the conclusion that Gigantopteridium encompasses the species previously treated as Cathaysiopteris yochelsonii as well as a new species, Gigantopteridium utebaturianum . The transfer of C . yochelsonii to Gigantopteridium yochelsonii suggests that Cathaysiopteris may represent a genus endemic to Cathaysia, limiting the biogeographical connection between the regions to Zeilleropteris, Gigantopteridium, Euparyphoselis, and Gigantonoclea .